THE EFFECT OF OKETANI MASSAGE ON BREASTFEEDING MOTHERS WITH BREAST MILK DAMS: A NARRATIVE REVIEW - Enny Nahumuri; Mardiana Ahmad; Aryadi Arsyad; Nur Aliya Arsyad (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
At the beginning of labor, the pain experienced after childbirth often makes the mother lazy to breastfeed her baby. Factors that affect failure in the process such as swollen breasts, mastitis, nipples, breast milk have not come out, and improper breastfeeding techniques. In the postpartum period, if the baby has not suckled and the breast glands are not emptied ideally, there will be a dam of milk, heat and hard, pain when groaned, nipples can flatten so that it can take the baby to suckle. This study aimed to find out the effect of Oketani massage on nursing mothers with breast milk dam. This research design is a narrative review to find and review articles from databases and theories that are descriptive. Search articles using databased ScienceDirect by entering the keyword